Answer:
1) They forgot to multiply 2 times (2x+5)
2) x-2 is not equal to -(x+2).
3) The correct expression is [tex]x-1-1+2x=1-3x[/tex]
4) The correct way is [tex]4(2x+3)=3(1-3x)[/tex]
Step-by-step explanation:
1) In this case they forgot to multiply 2 times (2x+5). Let's recall we need to multiply (2x+5) to all terms of the equation.
2) Here, x-2 is not equal to -(x+2). If we see -(x+2) = -x-2 using the distributive property.
3) After multiplying by (3x-2) we will have:
[tex]x-1-(1-2x)=1-3x[/tex]
Apply the distributive property again, we will have:
[tex]x-1-1+2x=1-3x[/tex]
So the correct term is 2x not -2x.
4) When we multiply by (1-3x)(2x+3) on each side of the equation, we will have something like this:
[tex]\frac{4(1-3x)(2x+3)}{(1-3x)}=\frac{3(1-3x)(2x+3)}{(2x+3)}[/tex]
If we see we can simplify the same terms on each side of the equation.
[tex]4(2x+3)=3(1-3x)[/tex]
This is the correct way to do this.
I hope it helps you!